UJARAN KEBENCIAN TERHADAP PRESIDEN MELALUI MEDIA SOSIAL TELAAH SIYASAH SYAR'IYYAH - Yuni, Gilli Sriwahyuni; Jamil (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
This study aims to find out how hate speech forms towards the president and how siyasi's views are regarding hate speech. In answering these problems, the author uses a juridical approach and a normative theological approach (syar'i). As for the method of collecting secondary data in the form of primary materials, secondary is done by reading literature, scientific papers, documents or books related to research. The results of the study show that actions that attack honor and humiliate someone, say bad words to other people, incite and spread false or false information where all actions that humiliate other people are forms of hate speech. Forms of hate speech such as insults, defamation, defamation, unpleasant acts, provocation, incitement, and spreading of fake news (hoaxes), are not the same as freedom of opinion or giving criticism. Even though there is freedom of opinion, this does not demean a person's honor and dignity in terms of ethnicity, religion, race, and intergroup aspects. Siyasi's views regarding hate speech, demeaning or humiliating acts, defamation, and even prejudice against other people are reprehensible actions, these actions can lead to slander, fake news and backbiting against individuals or other groups. These actions can harm other people, including the leader in this contest, the president himself.